A fragilidade dos relacionamentos contemporâneos: um olhar sobre Um copo de cólera, de Raduan Nassar - Joaes Cabral de Lima; Vanessa Riambau (Revista Principia, 2018)
The aim of this paper is to discuss the fragility of contemporary relationships through an investigation at Raduan Nassar’s novel “A cup of rage” (1992), for nowadays, in this liquid modernity, people do not want to take serious commitment, everything is legitimate, provided that there is a feeling of personal fulfillment,associated with pleasure satisfaction . This study is based both on Bauman’s work(2004) on the disintegration of human relations and on Hall’s work (1992) on the fragmentation of the modern individual through the new identities that arise so as to replace former identities that for so long have stabilized the social world